Advances in Blockchain Technology for Cyber Physical Systems - Maleh, Yassine; Tawalbeh, Lo'ai.; Motahhir, Saad.; Hafid, Abdelhakim Senhaji (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book helps discover various potential uses of blockchain that can be fruitful for cyber-physical system (CPS) applications. The authors provide a sampling of recent advances and ideas into the practical usage of blockchain technologies in addressing cyber-physical systems challenges and issues. The book provides a window into new theoretical and applied research related to blockchain technologies addressing cyber-physical systems including Internet of Things (IoT), Industrial Internet of Things (IIoT), Machine-to-Machine (M2M), and Industry 4.0. The book is applicable to researchers, professionals, academics, and students in communications engineering. Presents the latest discoveries and advances of blockchain techniques and applications for CPS; Analyzes and presents the state-of-the-art of blockchain technology and related technologies and methodologies in CPS; Proposes new models, practical solutions and technological advances related to blockchain for CPS applications.
Introduction -- Blockchain For Cyberphysical Systems -- Blockchain for Smart Transport application -- Design Laboratory Exercises for Blockchain Technology -- Blockchain for Industrial Internet of Things -- Blockchain for CPS Security -- Blockchain-based Technology for Industrial Control System -- Blockchain for Internet of Vehicles security -- When Healthcare Services Meet Blockchain Technology -- Searching for IoT Resources in Intelligent Transportation Cyber-Space (T-CPS) using Blockchain -- Blockchain-Based IoT Forensics -- Blockchain and Deep Learning Technologies in Smart Cities Surveillance using UAVs -- Blockchain to secure cyber infrastructure solution for future energy systems -- Conclusion.
Keywords: Cooperating objects (Computer systems).; Telecommunication; Computational intelligence; Artificial intelligence; Cyber-Physical Systems; Communications Engineering, Networks; Computational Intelligence; Artificial Intelligence